Developing an exploration model by investigating the geological controls on reservoir production within the Fort Scott limestone, Ness county, Kansas - Flenthrope, Christopher (Kansas State University, 2009)
Ness County, Kansas is situated along the western flank of the Central Kansas uplift, and has been an active center of oil exploration since the 1920’s. It currently ranks fourth among Kansas counties in oil production, largely from Mississippian-age carbonate reservoirs. Some production has been realized from lower Pennsylvanian-age carbonate formations, although the distribution of these reservoirs appears sporadic. The goals of this study were to develop an exploration model that predicts the development of reservoir conditions within the Marmatonage Fort Scott Limestone. A two-township area was studied to examine relationships between production rates and subsurface variations. No core was available through the Fort Scott, hence drill cuttings were thin-sectioned and examined under a petrographic microscope to see details of porosity type not easily visible under a binocular microscope. Production appears to be defined by stratigraphic variations in porosity controlled by original depositional environment. The best wells are within an oolitic limestone, with subsequent development of secondary, vuggy porosity. These conditions occur in bands along the Mississippian paleo-topographic highs. I interpret these bands to be ancient ooid shoals, with geometries and scales analogous to those previously reported from Lansing/Kansas City reservoirs in Russell County, Kansas. This study provides insights into production trends within the Fort Scott Limestone, and should be included during exploration in Ness County, Kansas.
Keywords: Fort Scott; Ness County; Oil; Ooids; Geology (0372)